First Report of the Black Soybean Weevil Rhyssomatus subtilis Fiedler (Coleoptera: Curculionidae) in Córdoba, Argentina. Crop Damage Estimation - Peralta, Celso Roberto; Rinero, Matías; Igarzábal, Daniel Antonio; De Rossi, Roberto Luis (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2025)
The black soybean weevil is an endemic pest in northwestern and northeastern Argentina, causing significant damage. The objective of this study was to confirm the presence of this species in Córdoba, describe symptomatology and evaluate the potential impact on the crop. Surveys were conducted in plots located in the north-central part of the province. Individuals were collected and a quantitative assessment of symptoms and damage was conducted. Twenty compound samples were taken from sectors showing different physiological appearances (green vs. yellowish). In each group, total pod number and damaged pod number allowed calculating damage percentage. Data were analyzed by ANOVA and Fisher’s test (α = 0.05). All collected individuals matched the morphological descriptions reported in the literature for the species Rhyssomatus subtilis Fiedler. Green plants had a higher proportion of damaged pods (0.89) and fewer pods (31.85) compared to yellowish plants (0.53 and 46.65, respectively). This relationship suggests a direct effect on biomass partitioning. Our finding remaps the pest’s distribution range, warning areas of high agricultural production in Córdoba and raising the need to link public-private actions to minimize its spread. Highlights: First record of Rhyssomatus subtilis in soybean fields in Córdoba Province, Argentina. The black soybean weevil was detected in five sites in the central-northern region, where no previous records existed. Detection was triggered by reports of pod damage. Identification was based on characteristic injury and the collection of larvae and adults, confirmed with expert input and literature. Damage assessment revealed physiological differences in affected plants. Severely damaged plants showed delayed senescence and symptoms consistent with green stem disorder. Pod injury by subtilis significantly reduced pod set. Statistical analysis showed marked differences in the number of pods between high- and low-damage areas.